From BIM to extended reality in AEC industry - Alizadehsalehi, Sepehr; Hadavi, Ahmad; Huang, Joseph Chuenhuei (Automation in construction, 2020)
In the Architecture, Engineering, and Construction (AEC) industry, Extended Reality (XR) technologies that simulate a construction project in a multidimensional digital model and present multiple aspects of a project can be a tremendous help in all stages of a project. This study aims to identify the outsourcing patterns for such technologies among construction project stakeholders. Currently, there is limited literature about XR technologies, and because of it, the sections containing the results of this study are as follows: (1) a concise review of the most recent VR, AR, and MR technologies in the design and construction industry; (2) an introduction to the most commonly used wearable XRs on the market in terms of features, ease of use, and their specifications; (3) a summary of the different methods and software used for converting the BIM model to VR, AR, and MR; and (4) finally, a case study included the integrated definition function (IDEF0) model that details how to convert the BIM model of the NASA-Mars habitat project to a VR and MR model that uses Oculus Rift, HTC Vive, Samsung HMD, and Microsoft HoloLens headsets. Overall, this study provides a comprehensive review regarding using XR to solve a variety of construction project management issues effectively and efficiently. More importantly, this study provides a roadmap for future efforts involving the implementation of XR technologies in the AEC industry. •This study reviewed the most relevant articles regarding BIM and XR (VR, AR, and MR) in the AEC industry.•This study proposed a BIM-based XR process/workflow to support construction projects.•This study evaluated the BIM-to-VR and BIM-to-MR process used by NASA-Mars habitat project case study.•This study identified the strengths and weaknesses of BIM-to-XR.•This study proposes processes which solve construction project management issues effectively and efficiently.